High-performance lithium battery silicon-carbon negative electrode material and preparation method thereof
By covering the surface of nano-silicon particles with nitrogen and/or phosphorus and a graphite layer to form a silicon-carbon composite material, the problems existing in traditional graphite and silicon-based anode materials in high-energy density batteries are solved, and efficient electrochemical performance and cyclic stability are achieved.
Patent Information
- Application Number
- CN202510041729.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-10
- Publication Date
- 2025-04-18
AI Technical Summary
The theoretical capacity of traditional graphite negative electrode materials is limited and cannot meet the needs of high-energy-density batteries. However, silicon-based negative electrode materials have problems such as large volume expansion and poor circulation performance during charging and discharging.
Silicon-carbon composite material is used as the negative electrode material of lithium batteries, and a multi-layer structure is formed by covering the carbon layer and graphite layer containing nitrogen and/or phosphorus elements on the surface of nano-silicon particles to improve conductivity and structural stability.
It effectively alleviates the volume expansion effect of silicon, improves lithium ion and electron conductivity, improves electrochemical performance, achieves good discharging and charging reversibility and cycle stability, and has a high specific capacity.
Smart Images

Figure CN119852363A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium ion battery negative electrode materials, and in particular to a high-performance lithium battery silicon-carbon negative electrode material and a preparation method thereof. Background Art
[0002] Lithium-ion batteries have attracted widespread attention due to their excellent performance, such as high energy density, high operating voltage, small size, light weight, no pollution, fast charge and discharge, and long cycle life. However, although traditional graphite-based negative electrode materials have a good layered structure and are suitable for the insertion and extraction of lithium ions, their theoretical capacity is limited and cannot meet the needs of high energy density batteries. Silicon-based negative electrode materials are considered to be potential materials to replace graphite negative electrodes due to their high theoretical capacity (up to 200mAh / g), but they have problems such as large volume expansion and poor cycle performance during the charge and discharge process. Summary of the invention
[0003] The purpose of the embodiments of the present application is to provide a high-performance lithium battery silicon-carbon negative electrode material and a preparation method thereof to solve the problems existing in the related art.
[0004] To achieve the above object, the present invention provides a high-performance lithium battery silicon-carbon negative electrode material and a preparation method thereof:
[0005] A high-performance lithium battery silicon-carbon negative electrode material, characterized in that the silicon-carbon negative electrode material comprises a silicon-carbon composite material, a first coating layer coated on the surface of the silicon-carbon composite material, and a second coating layer coated on the surface of the first coating layer; wherein the first coating layer is a carbon layer containing nitrogen and / or phosphorus elements, and the second coating layer is a graphite layer; the particle size of the nano-silicon particles is 70 to 250 nm, polyvinylidene chloride is used as a carbon source, and flake graphite is used as a carrier to prepare a silicon-carbon composite material with nano-silicon.
[0006] Preferably, the first coating layer is generated by polymer pyrolysis, and nitrogen ions and fluorine ions are incorporated into the coating layer during the pyrolysis process to form an amorphous carbon structure.
[0007] Preferably, the second coating layer is a commercial graphite layer, which provides high conductivity and structural stability.
[0008] Preferably, the preparation of nano silicon particles is as follows: first, polyvinylidene chloride is added to NN dimethylformamide, and after sufficient stirring, a transparent viscous liquid is formed, and then the nano silicon powder after ultrasound is added to fully mix the polyvinylidene chloride solution and the nano silicon powder to achieve a suspension state, the suspension is vacuum dried, the solid obtained after drying is subjected to high temperature cracking under argon protection, the product obtained by roasting is fully ground and sieved, and finally nano silicon particles with a carbon layer coated on the surface are obtained.
[0009] Preferably, the silicon-carbon composite material is prepared as follows: first, an appropriate amount of polyvinylidene chloride is weighed and added to NN dimethylformamide, and a transparent viscous liquid is formed after sufficient stirring. Then, the nano-silicon powder, polyvinylidene chloride solution and flake graphite after ultrasound are poured into a ball mill to mix them evenly, and then the mixed precursor is poured into a high-pressure reactor for hydrothermal reaction. After sufficient reaction, it is taken out and placed in a combustion boat, and then the reaction product is subjected to high-temperature cracking under the protection of xenon gas, and the product obtained by roasting is fully ground and sieved to finally obtain a composite material with flake graphite as the matrix and amorphous carbon wrapped around nano-silicon.
[0010] A method for preparing the high-performance lithium battery silicon-carbon negative electrode material according to claim 1, characterized in that it comprises the following steps:
[0011] (1) preparing micron silicon powder into nano silicon particles by thermal plasma method or ball milling method;
[0012] (2) annealing the sugar compound at 700 to 900° C. for 2 to 5 hours under the protection of an inert gas to obtain an amorphous carbon material containing nitrogen and / or phosphorus elements;
[0013] (3) mixing the nano-silicon particles obtained in step (1) and the amorphous carbon material obtained in step (2) in a mass ratio of 30% to 50%, adding the mixture to a planetary ball mill for ball milling at a ball-to-material ratio of 22 to 30:1, a ball milling speed of 350 to 600 r / min, and a ball milling time of 16 to 32 hours to obtain a binary precursor material;
[0014] (4) Add the binary precursor material obtained in step (3) and graphite in a mass ratio of 1:1 to 1:4 into a planetary ball mill and mill again. The ball milling conditions are the same as above and the ball milling time is 6 to 10 hours to obtain a silicon-carbon negative electrode composite material.
[0015] Preferably, the ball milling media of the planetary ball mill are zirconium oxide grinding balls.
[0016] The above technical scheme has the following beneficial effects: carbon materials have good electrical conductivity and structural stability, and are abundant in source and low in synthesis cost. A large number of research works have shown that carbon materials such as graphite, carbon nanotubes, pyrolytic carbon and new graphene can be compounded with silicon materials through different preparation methods, effectively alleviating the volume expansion effect of silicon, and improving the conductivity of lithium ions and electrons, and effectively improving its electrochemical performance. The technology of this scheme can solve the serious pulverization problem of silicon particles caused by the volume expansion effect of silicon, and achieve good discharge and charge reversibility and cycle stability: with high specific capacity. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0018] Figure 1 Schematic diagram of a silicon-carbon composite material provided in an embodiment of the present invention. DETAILED DESCRIPTION
[0019] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0020] A high-performance lithium battery silicon-carbon negative electrode material, characterized in that the silicon-carbon negative electrode material comprises a silicon-carbon composite material, a first coating layer coated on the surface of the silicon-carbon composite material, and a second coating layer coated on the surface of the first coating layer; wherein the first coating layer is a carbon layer containing nitrogen and / or phosphorus elements, and the second coating layer is a graphite layer; the particle size of the nano-silicon particles is 70 to 250 nm, polyvinylidene chloride is used as a carbon source, and flake graphite is used as a carrier to prepare a silicon-carbon composite material with nano-silicon.
[0021] Preferably, the first coating layer is generated by polymer pyrolysis, and nitrogen ions and fluorine ions are incorporated into the coating layer during the pyrolysis process to form an amorphous carbon structure.
[0022] Preferably, the second coating layer is a commercial graphite layer, which provides high conductivity and structural stability.
[0023] The preparation of nano silicon particles is as follows: first, polyvinylidene chloride is added to NN dimethylformamide, and after sufficient stirring, a transparent viscous liquid is formed, and then the nano silicon powder after ultrasound is added to make the polyvinylidene chloride solution and the nano silicon powder fully mixed together to reach the state of suspension, and the suspension is vacuum dried, and the solid obtained after drying is subjected to high temperature cracking under argon protection, and the product obtained by roasting is fully ground and sieved to finally obtain nano silicon particles with a carbon layer coated on the surface.
[0024] The specific steps are as follows:
[0025] (1) Dissolve polyvinylidene chloride in NN dimethylformamide, place in a beaker and stir magnetically for 10 hours to prepare a solution with a mass fraction of 5-10%, then add nano-silicon into the solution by ultrasonication for 0.8-1.5 hours and stir magnetically for 5-7 hours. The mass ratio of nano-silicon powder to polyvinylidene chloride is 4:1.
[0026] (2) The suspension in the beaker is then placed in a porcelain boat and dried in a vacuum oven to heat and volatilize the solvent N-N-dimethylformamide at 100-120° C. for 24-36 hours.
[0027] (3) The dried precursor is then pyrolyzed in an atmosphere of argon at 700°C for 2 h. After naturally cooling to room temperature, the obtained product is ground with an agate mortar and sieved for later use.
[0028] The silicon-carbon composite material is prepared as follows: first, an appropriate amount of polyvinylidene chloride is weighed and added to NN dimethylformamide. After sufficient stirring, a transparent viscous liquid is formed. Then, the nano-silicon powder, polyvinylidene chloride solution and flake graphite after ultrasound are poured into a ball mill to mix them evenly. Then, the mixed precursor is poured into a high-pressure reactor for hydrothermal reaction. After sufficient reaction, it is taken out and placed in a combustion boat. Then, the reaction product is subjected to high-temperature cracking under the protection of xenon gas. The calcined product is fully ground and sieved to finally obtain a composite material with flake graphite as the matrix and amorphous carbon wrapped around nano-silicon.
[0029] A method for preparing a high-performance lithium battery silicon-carbon negative electrode material comprises the following steps:
[0030] (1) preparing micron silicon powder into nano silicon particles by thermal plasma method or ball milling method;
[0031] First, weigh an appropriate amount of polyvinylidene chloride and dissolve it in NN dimethylformamide to make a solution with a mass fraction of 5%. Then weigh an appropriate amount of nano-silicon powder and flake graphite, add the prepared polyvinylidene chloride solution, nano-silicon powder and flake graphite into the ball mill, set the speed to 230rmin, and ball mill for 6.5h. Mechanical ball milling is an effective means to reduce the particle size of material particles and evenly mix materials. The ball mill used is a planetary ball mill. NN dimethylformamide is used as the liquid phase ball milling medium, and liquid phase grinding is adopted. The mass ratio of agate balls to materials is 2:1. After mechanical ball milling of nano-silicon powder and flake graphite at a certain speed and ball milling time, the two are fully mixed and reacted. The purpose of this step is to evenly mix the raw materials.
[0032] (2) annealing the sugar compound at 700 to 900° C. for 2 to 5 hours under the protection of an inert gas to obtain an amorphous carbon material containing nitrogen and / or phosphorus elements;
[0033] The ball-milled product was poured into a 50m polytetrafluoroethylene-lined high-pressure reactor, and the reactor was sealed and placed in a constant temperature drying oven, heated to 180°C, and the reaction temperature was maintained for 10 hours. The heating power of the constant temperature drying oven was turned off, and the reactor was naturally cooled to room temperature along with the furnace.
[0034] Take the precursor out of the reactor, move it to a porcelain boat, and then put it into a tube furnace. Tighten the valves on both sides and introduce argon to remove the air in the furnace. Then set the program: raise the temperature to 700-900℃ at 7℃min1 and maintain it for 2h, then let it cool naturally to room temperature. The high-temperature heat treatment in this article mainly refers to the high-temperature calcination of the prepared silicon-carbon precursor. The carbon source (PVDC) in the precursor is converted into amorphous pyrolytic carbon during the heat treatment process.
[0035] (3) mixing the nano-silicon particles obtained in step (1) and the amorphous carbon material obtained in step (2) in a mass ratio of 30% to 50%, adding the mixture to a planetary ball mill for ball milling at a ball-to-material ratio of 22 to 30:1, a ball milling speed of 350 to 600 r / min, and a ball milling time of 16 to 32 hours to obtain a binary precursor material;
[0036] (4) Add the binary precursor material obtained in step (3) and graphite in a mass ratio of 1:1 to 1:4 into a planetary ball mill and mill again. The ball milling conditions are the same as above and the ball milling time is 6 to 10 hours to obtain a silicon-carbon negative electrode composite material.
[0037] The high-temperature pyrolysis product is crushed in a mortar to obtain the desired silicon-carbon composite material, which can be used for electrode preparation and battery testing.
[0038] In the preparation process of silicon-carbon precursor, the main functions of high-energy ball milling are as follows: 1. Fully break up the agglomerated secondary nano-silicon particles and evenly disperse them on the surface or gap of flake graphite; 2. Appropriately crush the flake graphite to increase the specific surface area and pores of flake graphite, which is conducive to the dispersion and adhesion of nano-silicon particles; 3. Evenly coat the surface of flake graphite and nano-silicon particles with PVDC solution. The length of ball milling time has a great influence on the morphology of the material. If the ball milling time is too short, the nano-silicon particles and PVDC solution are not evenly dispersed, which will lead to uneven coating; if the ball milling time is too long, the impurities will increase, and the particle size of flake graphite will decrease, which will lead to an increase in the specific surface area of the material. The formation of SEI film will consume more lithium ions. In addition, if the ball milling time is too long, the structure of flake graphite will be destroyed, and the co-embedding effect of solvent will occur, resulting in faster capacity decay.
[0039] Those skilled in the art will readily appreciate other embodiments of the present application after considering the description and practicing the contents disclosed herein. The present application is intended to cover any modification, use or adaptation of the present application, which follows the general principles of the present application and includes common knowledge or customary techniques in the art that are not disclosed in the present application. The description and examples are intended to be exemplary only, and the true scope and spirit of the present application are indicated by the claims.
[0040] It should be understood that the present application is not limited to the precise structures that have been described above and shown in the drawings, and that various modifications and changes may be made without departing from the scope thereof. The scope of the present application is limited only by the appended claims.
Claims
1. A high-performance lithium battery silicon-carbon negative electrode material, characterized in that: The silicon-carbon negative electrode material comprises a silicon-carbon composite material, a first coating layer coated on the surface of the silicon-carbon composite material, and a second coating layer coated on the surface of the first coating layer; wherein the first coating layer is a carbon layer containing nitrogen and / or phosphorus elements, and the second coating layer is a graphite layer; the particle size of nano silicon particles is 70 to 250 nm, polyvinylidene chloride is used as a carbon source, flake graphite is used as a carrier, and the silicon-carbon composite material is prepared with nano silicon.
2. The high-performance lithium battery silicon-carbon negative electrode material according to claim 1, characterized in that: The first coating layer is generated by polymer pyrolysis, and nitrogen ions and fluorine ions are incorporated into the coating layer during the pyrolysis process to form an amorphous carbon structure.
3. The high performance lithium battery silicon-carbon negative electrode material according to claim 1 or 2, characterized in that: The second coating layer is a commercial graphite layer, which provides high conductivity and structural stability.
4. The high performance lithium battery silicon-carbon negative electrode material according to claim 1 or 2, characterized in that: The preparation of nano silicon particles is as follows: first, polyvinylidene chloride is added to NN dimethylformamide, and after sufficient stirring, a transparent viscous liquid is formed, and then the nano silicon powder after ultrasound is added to make the polyvinylidene chloride solution and the nano silicon powder fully mixed together to reach the state of suspension, and the suspension is vacuum dried, and the solid obtained after drying is subjected to high temperature cracking under argon protection, and the product obtained by roasting is fully ground and sieved to finally obtain nano silicon particles with a carbon layer coated on the surface.
5. The high performance lithium battery silicon-carbon negative electrode material according to claim 4, characterized in that: The silicon-carbon composite material is prepared as follows: first, an appropriate amount of polyvinylidene chloride is weighed and added to NN dimethylformamide. After sufficient stirring, a transparent viscous liquid is formed. Then, the nano-silicon powder, polyvinylidene chloride solution and flake graphite after ultrasound are poured into a ball mill to mix them evenly. Then, the mixed precursor is poured into a high-pressure reactor for hydrothermal reaction. After sufficient reaction, it is taken out and placed in a combustion boat. Then, the reaction product is subjected to high-temperature cracking under the protection of xenon gas. The calcined product is fully ground and sieved to finally obtain a composite material with flake graphite as the matrix and amorphous carbon wrapped around nano-silicon.
6. A method for preparing the high-performance lithium battery silicon-carbon negative electrode material according to claim 1, characterized in that: The following steps are involved: (1) preparing micron silicon powder into nano silicon particles by thermal plasma method or ball milling method; (2) annealing the sugar compound at 700 to 900° C. for 2 to 5 hours under the protection of an inert gas to obtain an amorphous carbon material containing nitrogen and / or phosphorus elements; (3) mixing the nano-silicon particles obtained in step (1) and the amorphous carbon material obtained in step (2) in a mass ratio of 30% to 50%, adding the mixture to a planetary ball mill for ball milling at a ball-to-material ratio of 22 to 30:1, a ball milling speed of 350 to 600 r / min, and a ball milling time of 16 to 32 hours to obtain a binary precursor material; (4) Add the binary precursor material obtained in step (3) and graphite in a mass ratio of 1:1 to 1:4 into a planetary ball mill and mill again. The ball milling conditions are the same as above and the ball milling time is 6 to 10 hours to obtain a silicon-carbon negative electrode composite material.
7. The method of high-performance lithium battery silicon-carbon negative electrode material according to claim 6, characterized in that: The ball milling medium of the planetary ball mill is zirconium oxide grinding balls.